MURNInets implementation towards sustainable township development in Malaysia - Ismail, Farrah Zuhaira; Yaman, Rostam; Rahman, Sarah; Marzukhi, Marlyana Azyyati; Ahmad, Noraini; Piyarat, Nanta (Faculty of Design & Architecture, UPM, 2024)
MURNInet (Malaysia Urban Indicators Network) is a framework developed by FDTCP (Federal Department of Town and Country Planning, Peninsular Malaysia) to measure the sustainability levels and performance of urban development in Malaysia. Since its launch in 2002, MURNInet set as a foundation to assess urban development in Malaysia. After review and refinement, it was rebranded as MURNInets (Malaysian Urban-Rural National Indicators Network for Sustainable Development) comprises of 6 sustainable dimensions, 20 sustainable themes and 39 sustainable indicators. The revised MURNInets provides wider agglomeration economies which offers larger prospects for knowledge and sharing information, effective provision of services especially in health and education, and also on cultural exchanges. The aims of this article is to examine the significance and achievement on the implementation of MURNInets by Malaysian Local Authorities. The method used in this study is semi-structured interviews with 8 registered urban planners of government agencies and government linked organisations. The outcomes suggested that all these sustainable factors are important for societal development, empowerment of public community, wellbeing, cultural solidification, transformation and cosmopolitanism. Generally, all dimensions, theme and indicators were achieved in the implemented score.